A fatal outbreak of neonatal sepsis caused by mcr-10-carrying Enterobacter kobei in a tertiary care hospital in Nepal. (July 2022) - Manandhar, S.; Nguyen, Q.; Pham, D.T.; Amatya, P.; Rabaa, M.; Dongol, S.; Basnyat, B.; Dixit, S.M.; Baker, S.; Karkey, A.
Summary: Background: Enterobacter kobei is an emerging cause of outbreak of nosocomial infections in neonatal intensive care units (NICUs). Between July and September 2016, a NICU in a tertiary care hospital of Nepal observed an abrupt increase in the number of neonatal sepsis cases caused by Enterobacter spp. infecting 11 out of 23 admitted neonates, five of whom died of an exacerbated sepsis. Aim: To confirm the suspected outbreak, identify environmental source of infection, and characterize genetic determinants of antimicrobial resistance (AMR) and virulence of the pathogen. Methods: Whole-genome sequencing of all Enterobacter spp. isolated from blood cultures of septic neonates admitted to NICU between May 2016 and December 2017 was performed. Also, an environmental sampling was intensified from fortnightly to weekly during the outbreak. Findings: The genomic analysis revealed that 10 out of 11 non-duplicated E. kobei isolated from neonatal blood cultures between July and September 2016 were clonal, confirming the outbreak. The isolates carried AMR genes including bla AmpC and mcr-10 conferring reduced susceptibility to carbapenem and colistin respectively. The environmental sampling, however, failed to isolate any Enterobacter spp. Reinforcement of aseptic protocols in invasive procedures, hand hygiene, environmental decontamination, fumigation, and secluded care of culture-positive cases successfully terminated the outbreak. Conclusion: Our study underscored the need to implement stringent infection control measures to prevent infection outbreaks. For the first time, we report the emergence of carbapenem and colistin non-susceptible E. kobei carrying mcr-10 gene as a cause of nosocomial neonatal sepsis in a NICU.